If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(-3y + 4) = -85 Reorder the terms: 5(4 + -3y) = -85 (4 * 5 + -3y * 5) = -85 (20 + -15y) = -85 Solving 20 + -15y = -85 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + -15y = -85 + -20 Combine like terms: 20 + -20 = 0 0 + -15y = -85 + -20 -15y = -85 + -20 Combine like terms: -85 + -20 = -105 -15y = -105 Divide each side by '-15'. y = 7 Simplifying y = 7
| 5(-3+4)=-85 | | x^2+60x-10000=0 | | y=3E-13x^8 | | 2x+0=24 | | (6+3)+2= | | .5h=1.28571428571429 | | 3(2t-5)=33 | | (4-w)(4w-9)=0 | | 2y-x=5+2x | | 4s+2+7=19+10 | | (k+4)(k+1)=10 | | .3x-.5=3.7 | | 3x+3=-45 | | -15(4w-5)=-105 | | 14y=7x+28 | | x(56-2x)= | | 3w^2+13w+4=0 | | 12v+12-8v=40 | | 3*4*9= | | x^2+y^2-16x-12y+51=0 | | 3*0*9= | | 21n(x+4)=6 | | 12*0= | | (P-2)(3p+7)= | | x=7+2t | | 2.75d-4.5=2.25d+3.5 | | x-7=2t | | 3*-3*9= | | 7x-7w+2y+5w+5x+9y= | | 10r^2-53r+36=0 | | 7.2x-14.1=7.5 | | 7p^2-2p=5 |